2020
DOI: 10.1007/s42770-020-00327-9
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Sporothrix activity of ibuprofen combined with antifungal

Abstract: The in vitro activity of ibuprofen, a nonsteroidal anti-inflammatory drug, was evaluated against Sporothrix brasiliensis and S. schenckii, either alone or in combination with amphotericin B, itraconazole, or terbinafine. The inhibitory activity of ibuprofen as a single agent was determined according to minimum inhibitory concentration (MIC) values, while the effect of ibuprofen combined with amphotericin B, itraconazole, or terbinafine was estimated by microdilution checkerboard methodology. The ultrastructura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…In addition, aspirin and ibuprofen combined with fluconazole, caspofungin, and amphotericin B have effects on fungi (Ogundeji et al 2016 ; Yang et al 2016 ). Ibuprofen also has anti- Sporothrix activity singly (median MIC of 256 μg/mL) or in combination with antifungal agents including amphotericin B, itraconazole, and terbinafine (Borba-Santos et al 2021 ). Diclofenac sodium can downregulate the expression of Ef-1 gene, which is involved in cellular RNA transport, cell cycle, and apoptosis (Alves et al 2015 ), thus resulting in a reduction in the formation of A. fumigatus filaments (Nargesi and Rezaie 2018 ).…”
Section: Non-steroidal Anti-inflammatory Drugsmentioning
confidence: 99%
“…In addition, aspirin and ibuprofen combined with fluconazole, caspofungin, and amphotericin B have effects on fungi (Ogundeji et al 2016 ; Yang et al 2016 ). Ibuprofen also has anti- Sporothrix activity singly (median MIC of 256 μg/mL) or in combination with antifungal agents including amphotericin B, itraconazole, and terbinafine (Borba-Santos et al 2021 ). Diclofenac sodium can downregulate the expression of Ef-1 gene, which is involved in cellular RNA transport, cell cycle, and apoptosis (Alves et al 2015 ), thus resulting in a reduction in the formation of A. fumigatus filaments (Nargesi and Rezaie 2018 ).…”
Section: Non-steroidal Anti-inflammatory Drugsmentioning
confidence: 99%
“…Regarding in vitro activity, 25 articles described the inhibitory activity of 28 drugs against S. brasiliensis (100% fungal-inhibition criterion): 20 chemicals and 8 repurposed drugs [ 48 , 49 , 51 , 53 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. Data about the MIC for each individual drug are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, new options for sporotrichosis treatment, mainly focusing on S. brasiliensis , are urgent. Various in vitro and in vivo studies have described new potential drugs against this Sporothrix species [ 48 , 49 , 50 ]. Chemical drugs are a promising area for research, with data regarding stability and other pharmacological characteristics of the molecules [ 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, different studies have demonstrated in vitro activity of some anti-inflammatory components. Borba-Santos et al [5] discuss here the in vitro activity of ibuprofen, a nonsteroidal anti-inflammatory drug, against S. brasiliensis and S. schenckii.…”
mentioning
confidence: 99%